The Pengaruh Harga, Keamanan, dan Promosi terhadap Keputusan Pembelian pada Toko Online Tokopedia di Jabodetabek - LANANG ANDHIKA PERWIRA BAYUAJI; Denny Septa Haryanti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study was to examine and analyze the influence of price, security, and promotion on purchasing decision of Tokopedia in Jabodetabek. The object in this study is Tokopedia. The sampling technique used in this study was purposive sampling with a sample of 150 sample. The data analysis method that used in this study was multiple linear regression and using SPSS 25th to analyze the data. The results of this study shows that price and promotion has a effect on purchasing decisions, on the other hand, security does not affect purchasing decisions.